Избранное: поэзия / Марина Цветаева - Цветаева Марина Ивановна (Эксмо, 2015)
Экземпляры: ф.12 (20160304) / Инвентарный номер: 52697 / Цена: 216.00. / Сис.шифр: Р2 / Авт.знак: Ц 27 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5